2008
DOI: 10.1002/nau.20613
|View full text |Cite
|
Sign up to set email alerts
|

Desmopressin, as a “designer‐drug,” in the treatment of overactive bladder syndrome

Abstract: Antidiuresis, using oral desmopressin tablets, is a novel, feasible and safe (short-term basis) method of treatment for adults with OAB, and could be considered in the armamentarium of drugs available for the treatment of OAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Some recent studies have reported the efficacy of desmopressin in patients with OAB [10,11]. The rationale for use of desmopressin in the treatment of OAB patients is that through a decrease in urine production, desmopressin will increase the time taken to reach functional bladder capacity between daytime voids, thereby reducing frequency and urgency and benefiting adults suffering from OAB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have reported the efficacy of desmopressin in patients with OAB [10,11]. The rationale for use of desmopressin in the treatment of OAB patients is that through a decrease in urine production, desmopressin will increase the time taken to reach functional bladder capacity between daytime voids, thereby reducing frequency and urgency and benefiting adults suffering from OAB.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent clinical trials have reported promising results showing improvement of symptoms of daytime frequency and urgency in patients with OAB with desmopressin through decreases in renal urine production and increases in bladder filling time [10,11]. However, there have been no reports concerning the effect of desmopressin combined with anticholinergics.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that DDAVP, a vasopressin analog, prolongs bladder filling time thereby increasing the time to reach maximum capacity; this increases time between voids, allowing patients to remain dry though the night [4,22]. It is generally considered first-line therapy for enuresis due to its rapid onset and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A proof-of-concept, double-blind, placebo-controlled, randomized, cross-over study included 88 adult patients with OAB. 14 The investigators reported that treatment with desmopressin 0.2 mg was associated with a significant reduction in the number of voids over eight hours (3.2 vs. 4.2; p < 0.001). There was also a significant increase in the time to first urgency episode and a decrease in the number of urgency episodes for desmopressin compared to placebo (p < 0.003).…”
Section: Desmopressinmentioning
confidence: 99%